KEDUDUKAN HUKUM TERHADAP PERJANJIAN PINJAM MEMINJAM UANG YANG BERBASIS ONLINE (FINTECH) DALAM PERSPEKTIF PERJANJIAN KONVENSIONAL - Indriani, Safitri (Bahasa Indonesia, 2022)
This research will discuss the legal position of online-based lending and borrowing agreements (Fintech) from the perspective of conventional agreements. This online-based lending and borrowing activity must be accompanied by a legal umbrella that is fair and with permanent legal certainty, in order to create healthy competition and provide convenience for creditors and debtors in this online-based lending and borrowing activity. The convenience in question is that the debtor gets a guarantee related to the confidentiality of personal data and all forms of guarantees because it is spread in public very easily through online media. Likewise, creditors must feel calm and safe in running their business, because the online-based borrowing process is not done face-to-face, so the process of checking or checking guarantees and the ability to pay becomes a very difficult thing to analyze. The research method used is a normative research method that comes from primary and secondary legal data. From the results of research conducted can obtain results, namely: 1). The legal position of information technology-based lending and borrowing agreements is an underhand deed which, if you want to use it, you have to go through the courts, 2). There must be arrangements regarding interest rates, protection of the identity of the parties, and regarding witnesses.